Non-canonical transcription initiation: the expanding universe of transcription initiating substrates - Barvík, Ivan; Rejman, Dominik; Panova, Natalya; Šanderová, Hana; Krásný, Libor (FEMS microbiology reviews, 2017)
RNA polymerase (RNAP) is the central enzyme of transcription of the genetic information from DNA into RNA. RNAP recognizes four main substrates: ATP, CTP, GTP and UTP. Experimental evidence from the past several years suggests that, besides these four NTPs, other molecules can be used to initiate transcription: (i) ribooligonucleotides (nanoRNAs) and (ii) coenzymes such as NAD+, NADH, dephospho-CoA and FAD. The presence of these molecules at the 5΄ ends of RNAs affects the properties of the RNA. Here, we discuss the expanding portfolio of molecules that can initiate transcription, their mechanism of incorporation, effects on RNA and cellular processes, and we present an outlook toward other possible initiation substrates.
Keywords: Coenzymes; iniciace genetické transkripce; Transcription Initiation, Genetic; RNA stability; coenzymes; koenzymy; non-canonical transcription initiation; Oligonucleotides; RNA polymerase; nicotinamide adenine dinucleotide (NAD+); oligonukleotidy; transcription initiating substrate